Isolation, nucleotide sequence, and preliminary characterization of the Escherichia coli K-12 hemA gene. - Verkamp, E (1989)
The Escherichia coli hemA gene, essential for the synthesis of 5-aminolevulinic acid (ALA), was isolated and sequenced. The following criteria identified the cloned gene as hemA. (i) The gene complemented a hemA mutation of E. coli. (ii) The gene was localized to approximately 26.7 min on the E. coli chromosomal linkage map, consistent with the location of the mapped hemA locus. Furthermore, DNA sequence analysis established that the cloned gene lay directly upstream of prfA, which encodes polypeptide chain release factor 1. (iii) Deletion of the gene resulted in a concomitant requirement for ALA. The hemA gene directed the synthesis of a 46-kilodalton polypeptide in maxicell experiments, as predicted by the coding sequence. The DNA and deduced amino acid sequences of the E. coli hemA gene displayed no detectable similarity to the ALA synthase sequences which have been characterized from a variety of organisms, but are very similar to the cloned Salmonella typhimurium hemA sequences (T. Elliott, personal communication). Results of S1 nuclease protection experiments showed that the hemA mRNA appeared to have two different 5' ends and that a nonoverlapping divergent transcript was present upstream of the putative distal hemA transcriptional start site.